(untitled) (Journal of Educational Sciences, 2016)
The article considers the important theoretical problem of the classification of parts of speech. The author familiarizes the readers with the system of parts of speech in the Azerbaijani language and shows a technique of work on them. The Azerbaijani language has the specific phonetic and grammatical structure. In morphological structure of the Azerbaijani language there are the following parts of speech: noun, adjective, numerals, pronouns, adverbs, verbs (remarkable); послелог, Union, particle, modal words, interjection (office). The noun possesses the categories of number, possessiveness, case, expression; has six cases. The remarkable words of the official part of speech differ in three ways: 1) have no independent of lexical meaning, 2) when all usages retain their morphological structure, 3) are not used independently. Formation of grammatical concepts of the part of speech of students Azerbaijanis is one of the most important directions in the study of morphology, providing digestion of pupils of grammar. A means of developing the logical and grammatical thinking of schoolchildren (the ability to abstract, to generalize, typed, compare the phenomena of language, comparing the total private and specific) and the means of formation of conscious perception of their own speech and the speech of others is the basis for continuous speech improvement of schoolchildren.